Optimization of Production Scheduling on the Nct Vipross 255 Machine Using the Heuristic Priority Dispatching Rules Method and Overall Equipment Effectiveness - Oloan; Budhi Muliawan Suyitno; Susanto Sudiro (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
Scheduling is defined as the process of allocating resources or machines – machines for scheduling a set of tasks in a specific time period, then based on the Priority of the job one Dispacthing Rules have a high priority for the further processed on the machine. This research uses a scheduling and Dispatching Rules Such As Oee The best production scheduling results i.e. use rules Such As the Total value of Flow Time of 1708.61 minutes into 1288.14 minutes, Average Flow Time of 170.86 minutes, Utilitasn minutes, 128.81 became the engine of the menigkat 20% to 26% and the average queue job from 5.06 seconds be 3.81 minutes. The results of the second best production scheduling also uses the rules to all the components of the job SUCH AS the total value of maximum Flow time of the 594.35 minutes be 348.17 seconds, the average completion time maximum 34.96 seconds, becoming 23.7 seconds and the average queue job maximum 7.23 minutes be 5.12 seconds, the result of the calculation of the value of the Avaibility Rate (AR) 5.86%, the value of the performance Rate (PR) 91.34%, Rate Of Quality 97,15, Overal Eqiupment Effektivines (OEE) 83.76%